Konsep Roh Suci Menurut Islam dan Kristian: The Concept of Holy Spirit in Islam and Christian - Badhrulhisham, Adam; Mohd Khambali @ Hambali, Khadijah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
In the context of language, Rūh al-Qudus or Holy Spirit carries the same meaning. This concept exists in Islam and Christianity as the religions that have a distinct relationship from the context of history and belief. But there is a big difference between the concepts that brought up confusion and misunderstanding. It also has a direct impact in interfaith life. This article aims on explaining the differences using comparative qualitative methods. In general, it can be seen that these two concepts have a very significant difference, namely, in divine concepts, even sharing similar terms. Rūh al-Qudus in Islam refers to the angel Gabriel while the Holy Spirit refers to the substance of God. This should be explained to avoid any confusion and misunderstanding in the context of interfaith relation.